TAKING TURNS AND "CRACKING NOSES:" DIALOGIC POTENTIAL IN ONE FIFTH-GRADE CLASSROOM. - Wrenn, Melissa (Journal of Ethnographic & Qualitative Research)
The purpose of the present case study was to examine the instructional practices that influence the frequency and quality of dialogic opportunities in one fifth-grade classroom. The present study occurred during a 14-week period of time. Sociolinguistic theory and situated learning theory provided a framework for interpreting text-based discussions in a variety of group settings in a classroom located in a rural, Title I school. Data were analyzed thematically and conducted secondary analysis using a dialogic rating assessment. The results from the present study show positive and negative factors that influence talk quality. Decentering with scaffolding and agentive talk moves promote dialogic talk. Problems with text encourage unsanctioned talk that inhibits learning. These findings validate existing research on dialogic talk, as well as raise questions regarding the problems of unsanctioned talk. Encouraging the development of pedagogical language knowledge and application of social-emotional learning to existing practices may prompt more successful development of dialogic pedagogy in elementary classrooms.